PERBEDAAN KEJADIAN DEPRESI PADA KARYAWAN PEREMPUAN DENGAN LAMA KERJA PANJANG DAN LAMA KERJA PENDEK DI PERUSAHAAN BISMA GROUP DENPASAR - Putu Stephanie Apriliana Hardika; Thomas Eko Purwata (E-Jurnal Medika Udayana, 2017)
High prevalence of depression at productive ages placed this neuropsychiatry disturbance as one of the most often disease occurs at workplace. Several factors are contributed in the occurrence of depression, one of them is working time. The aim of this study was to determine the difference in prevalence of depression among female workers with long-time working and short-time working. This study was done at Bisma Group Company Denpasar by cross-sectional approached. All female workers were interviewed in order to get samples which fulfill inclusion and exclusion criteria. Depression status was measured by Hamilton Depression Rating Scale. Among 45 samples, 71.11% is developing depression. The prevalence of depression is found higher among female workers with long-time working: (1) depression with long duration of work is about 87.5% and (2) depression with long job tenure is about 86.4%. This study also found the significant difference in prevalence of depression with duration of work (p = 0.01) and job tenure (p = 0.027). The conclusion is the long-time working could increase the prevalence ratio of depression among female workers. In other words, there is significant difference in proportion of depression among female workers with long-time working and short-time working at Bisma Group Company Denpasar. Keywords: female workers, working time, depression